The sedimentary record of wet and dry eolian systems in the Cretaceous of Southeast Brazil: stratigraphic and paleogeographic significance - Mescolotti, Patricia Colombo [UNESP]; Varejao, Filipe Giovanini [UNESP]; Warren, Lucas Verissimo [UNESP]; Bernardes Ladeira, Francisco Sergio; Fonseca Giannini, Paulo Cesar; Assine, Mario Luis [UNESP] (Soc Brasileira Geologia, 2019)
Sedimentologic and stratigraphic studies of paleo-deserts from the Brazilian Cretaceous are of great potential to understand the paleoclimate and paleogeography of Gondwana during its final rifting stage. Herein, we describe and discuss two depositional units characterized by two distinct eolian systems that are bounded by a long-lived unconformity. The Lower Unit (Barremian/Aptian) encompasses a wet eolian system composed of dune, interdunes, and ephemeral alluvial deposits. A continuous paleosol horizon in the upper part of the Lower Unit records dune stabilization and end of eolian accumulation, in a period of climate amelioration possibly in the late Aptian. The stratigraphic gap proposed for the unconformity (Cenomanian to Coniacian) coincides with the Cretaceous Thermal Maximum. The Upper Unit (Santonian?/ Campanian) comprises dune fields of a dry eolian system capped by the Mata da Corda volcanic rocks. Cross stratification dip directions from both eolian systems shows transport towards SSW. Paleo-winds coming from the northeast quadrant reveal that the continental breakup and drifting had little influence on the surface winds in this Gondwana sector. The Upper Cretaceous paleo-winds are coherent with global paleo-circulation models, based on a high-pressure cell over the South Atlantic proto-ocean, favoring desertification in the inner portion of the southwestern Gondwana.
Keywords: Areado Group; Eolian systems; Cretaceous paleo-winds; Sanfranciscana Basin